Pelatihan Pemasangan Panel Surya Sebagai Sumber Listrik Di Objek Wisata Alam Punthuk Ngepoh Brajan - Muhammad, Suyanto; Pambudi, Prastyono Eko; Syafriyudin (DHARMA BAKTI, 2022)
For lovers of the outdoors and looking for tranquility, the Puthuk Ngepoh tourist attraction is located in Brajan Hamlet, Banjararum, Kalibawang Kulon Progo, which is in the Menoreh Hills. The location is 45 km from downtown Jogjakarta. Managed by a tourism awareness group (POKDARWIS), it can be a choice of destination to fill the weekend. One of the existing problems, is the constraint on electricity which is more economical. Therefore, the authors seek to Install Solar Panels (PLTS), as an alternative source of electricity by utilizing sunlight as a producer of electrical energy, which is environmentally friendly. This is expected to be a solution for the burden of lighting at tourist sites. Batteries are one option to store electrical energy, from solar panels. In observations, the battery is charged by solar panels that generate voltage by converting solar energy into electrical energy. The voltage generated from the solar panels ranges from 14.8 to 17.5 volts DC. The solar panels used are of the type Polycrystalline (Poly-crystalline) with a power of 100wp. The measurement results show that the solar panel current and voltage are ± 17V, the distribution to the battery is regulated by the solar charger controller (SCC), an average of 13.5V. Change the DC to AC voltage using an inverter. This shows that after the battery is charged for 2-3 hours, it can operate for 3 hours with an inverter output voltage of 220-176volt AC. Voltage and current will start to increase at 07.00 WIB, maximum at 10.00-13.00 WIB, starting to decrease until the afternoon.